PENGARUH KUALITAS TIDUR IBU TERHADAP PRAKTIK PEMBERIAN ASI PADA BAYI - Fauziah, Siska Febrina; Lestaluhu, Viqy; Kurniawati, Imas (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2024)
Sleep deprivation and fatigue experienced by new mothers are often considered normal in society. However, rest and sleep are crucial for postpartum mothers to aid in physical recovery and maintain emotional balance. Additionally, lack of sleep can lower prolactin concentration in the blood, which may reduce breast milk production. This study aims to determine the influence of maternal sleep quality on breastfeeding practices in infants. The research was conducted using a cross-sectional method on mothers with babies aged 0 to 2 years, utilizing Pittsburgh Sleep Quality Index (PSQI). The number of respondents in this study is 214, recruited through social media. Data were analyzed using chi-square test and odds ratio (OR). The results showed that the majority of mothers felt their sleep quality was quite good (71%), but based on the PSQI scores, most respondents actually had poor sleep quality (79%). Nevertheless, nearly three-quarters of the respondents in this study managed to provide exclusive breastfeeding. The statistical analysis revealed a p-value of 0.040 and an OR of 2.58, indicating that the maternal sleep quality significantly affects the breastfeeding practices. Mothers with good sleep quality are 2.58 times more likely to exclusively breastfeed compared to mothers with poor sleep quality. Therefore, it is important to pay attention to the mother's rest needs to ensure better health outcomes for both mother and child.